2013
DOI: 10.1111/epi.12223
|View full text |Cite
|
Sign up to set email alerts
|

Can structural or functional changes following traumatic brain injury in the rat predict epileptic outcome?

Abstract: Summary Purpose Post-traumatic epilepsy (PTE) occurs in a proportion of traumatic brain injury (TBI) cases, significantly compounding the disability, risk of injury, and death for sufferers. To date, predictive biomarkers for PTE have not been identified. This study used the lateral fluid percussion injury (LFPI) rat model of TBI to investigate whether structural, functional, and behavioral changes post-TBI relate to the later development of PTE. Methods Adult male Wistar rats underwent LFPI or sham-injury.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
127
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(141 citation statements)
references
References 54 publications
14
127
0
Order By: Relevance
“…As shown in Fig. 1, volumetric and morphological changes in the hippocampus and other limbic structures have been reported in both SE [26][27][28][29] and FPI models [11,23,30,31]. However, these changes are typically preceded by abnormalities identified by other more sensitive neuroimaging methods [11,23,[28][29][30][31].…”
Section: Volumetric and Morphological Analysesmentioning
confidence: 87%
See 3 more Smart Citations
“…As shown in Fig. 1, volumetric and morphological changes in the hippocampus and other limbic structures have been reported in both SE [26][27][28][29] and FPI models [11,23,30,31]. However, these changes are typically preceded by abnormalities identified by other more sensitive neuroimaging methods [11,23,[28][29][30][31].…”
Section: Volumetric and Morphological Analysesmentioning
confidence: 87%
“…As seen in Fig. 1, [18F]FDG-PET following FPI in rats has also identified acute and persistent hypometabolism that preceded significant structural atrophy [11,30], and may predict the later onset of PTE [11]. While further research is clearly required, and other limitations must be considered [62], these findings, together with the ability to assess other relevant pathophysiological processes in vivo, make PET a valuable experimental tool in the investigation of epileptogenesis.…”
Section: Positron Emission Tomographymentioning
confidence: 90%
See 2 more Smart Citations
“…Recently, Schultz et al [67] reported that abnormalities in the surface morphology of the ipsilateral hippocampus present at 1 week after lateral FPI predicted the occurrence of epilepsy 6 months after TBI [67]. We recently investigated whether quantitative T2, T1ρ, and diffusion (Dav) assessed with MRI at 9 days, 23 days, or 2 months after TBI in the peri-lesional cortex, thalamus, and hippocampus would predict seizure susceptibility in the PTZ test at 12 months after TBI [68].…”
Section: Biomarkers For Epileptogenesis After Brain Injurymentioning
confidence: 99%